In vitro and in vivo production and split-intein mediated ligation (SIML) of circular bacteriocins - Peña, Nuria; Bland, Michael J.; Sevillano, Ester; Muñoz-Atienza, Estefanía; Lafuente, Irene; Bakkoury, Mohamed El; Cintas, Luis M.; Hernández, Pablo E.; Gabant, Philippe; Borrero, Juan (Frontiers in Microbiology, 2022)
Circular bacteriocins are antimicrobial peptides produced by bacteria that after synthesis undergo a head-to-tail circularization. Compared to their linear counterparts, circular bacteriocins are, in general, very stable to temperature and pH changes and more resistant to proteolytic enzymes, being considered as one of the most promising groups of antimicrobial peptides for their potential biotechnological applications. Up to now, only a reduced number of circular bacteriocins have been identified and fully characterized, although many operons potentially coding for new circular bacteriocins have been recently found in the genomes of different bacterial species. The production of these peptides is very complex and depends on the expression of different genes involved in their synthesis, circularization, and secretion. This complexity has greatly limited the identification and characterization of these bacteriocins, as well as their production in heterologous microbial hosts. In this work, we have evaluated a synthetic biology approach for the in vitro and in vivo production combined with a split-intein mediated ligation (SIML) of the circular bacteriocin garvicin ML (GarML). The expression of one single gene is enough to produce a protein that after intein splicing, circularizes in an active peptide with the exact mass and sequence as native GarML. In vitro production coupled with SIML has been validated with other, well described and not yet characterized, circular bacteriocins. The results obtained suggest that this synthetic biology tool holds a great potential for production, engineering, improving and testing the antimicrobial activity of circular bacteriocins.